Analisis Tingkat Kekritisan Lahan Kawasan Budidaya Pertanian Kabupaten Sleman Tahun 2016 - Wijayanti, Dessy Ika; , Ir. Taryono, M. Si (2017)
This study analyzes the degree of criticality of the land on the farm area in Sleman district. The purpose of this study was to determine the critical level Shareable existing land on degraded land farm area of Sleman Regency as well as knowing the right alternative applied land management. The method used in this study is a survey method. This study uses Geographic Information System analysis with weighted tiered quantitative approach and analysis descriptively. The weighted tiered quantitative approach used to process parameters critical level of agricultural land cultivated area so that land can be determined critical level. Parameters used in pennetuan critical level land, among others, land management, agricultural productivity, slope, erosion, and Shareable rocks. Descriptive analysis is used to determine the critical alternative land management. The results showed that: (1) The level of criticality land farm area consists of Sleman district not critical land with an area of 671.88 ha (20.82%), the critical potential 19250.85 ha (64.88%), somewhat critically 3490 , 85 ha (11.76%), the critical 687.02 Ha (2:32%), and very critical 65.32 Ha (12:22%). (2) Alternative land management farm area is based on the level of criticality. To land not critical efforts are needed to maintain the land, one with a boundary LP2B land. Critical potential land requires soil conservation in order to become more productive land and not be degraded lands. Land that has experienced the critical need of conservation and rehabilitation so that the land can be used again. Keywords: Land, Land Criticality, Region Agriculture, Geographic Information Systems.